Uncertainty, investment and productivity with relational contracts - Malcomson, J (University of Oxford, 2021)
This paper shows that, in the presence of relational contracts, an increase in uncertainty with no change in factor prices reduces capital investment and productivity in the long run even if the parties are otherwise risk neutral. Recent literature on the effect of uncertainty on investment has focused on the option value arising from irreversibility of investment and on the impact of financial risk on the cost of capital. For the option value model, however, Bloom et al. (Econometrica, 2018) find that a negative aggregate shock to total factor productivity, not just an increase in its uncertainty, is required to capture the drop in investment and productivity associated with the increase in uncertainty in recessions. With the cap ital cost model, the reduction in investment lasts only as long as the higher capital cost is sustained. The current paper first develops a relational contract model to demonstrate the impact of uncertainty on investment and how the effect depends on whether the investment is general or specific. To illustrate how taking account of relational contracts can help capture the effect of uncertainty on investment empirically, it then uses a specification calibrated with parameters from Bloom et al. (Econometrica, 2018) to show that this model can generate effects on investment of the magnitude of the negative aggregate shock in that paper purely with an increase in uncertainty with no change in factor prices.